A feasibility study of dynamic stress analysis inside a running internal combustion engine using synchrotron X-ray beams - Baimpas, N; Drakopoulos, M; Connolley, T; Song, X; Pandazaras, C; Korsunsky, A (2013)
The present investigation establishes the feasibility of using synchrotron-generated X-ray beams for time-resolved in situ imaging and diffraction of the interior components of an internal combustion engine during its operation. The demonstration experiment was carried out on beamline I12 (JEEP) at Diamond Light Source, UK. The external hutch of the JEEP instrument is a large-scale engineering test bed for complex in situ processing and simulation experiments. The hutch incorporates a large capacity translation and rotation table and a selection of detectors for monochromatic and white-beam diffraction and imaging. These capabilities were used to record X-ray movies of a motorcycle internal combustion engine running at 1850 r.p.m. and to measure strain inside the connecting rod via stroboscopic X-ray diffraction measurement. The high penetrating ability and high flux of the X-ray beam at JEEP allowed the observation of inlet and outlet valve motion, as well as that of the piston, connecting rod and the timing chain within the engine. Finally, the dynamic internal strain within the moving connecting rod was evaluated with an accuracy of ∼50 × 10-6. © 2013 International Union of Crystallography.